Systematic review of flexibility tests in gymnastics - Vernetta-Santana, M.; Peláez-Barrios, E. M.; López-Bedoya, J. (Journal of Human Sport & Exercise, 2022)
The aim of this study was to review the tests used to measure flexibility in gymnastic disciplines. The search was conducted on PubMed, WOS, Scopus, Sport Discus and Google Scholar databases, and included studies in English and Spanish that assessed flexibility in gymnasts and were published between January 2005 and March 2020. Twenty-seven manuscripts were selected, rhythmic and women`s artistic gymnastics being the most frequently studied disciplines. Flexibility was most commonly assessed in the hip and shoulder joints. Within the wide variety of tests performed, the most commonly used ones were the split, shoulder flexibility, bridge and sit-and-reach tests. Linear measurements were usually used, followed by the angular ones. In conclusion, in spite of flexibility being a determining capacity in gymnastic disciplines, several studies did not provide information on the validity of their results. Further studies including validated tests applied to larger samples and using longitudinal approaches are needed, with the aim to confirm test predictive validity and to allow for greater generalisation.